Memahami Tikrār Lafdzi Dalam Kitab Tafsir Al-Kassyaaf Karya Az-Zamakhsyari Pada Surah Al-Insyirah Ayat 5-6 - Annisa Inggria; Babang Prima Nugraha; Aisyah Nurul Fadhilah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article was written to analyze the tikrar lafdzi in Surah Al-Insyirah verses 5 and 6 and understand the meaning or purpose of repeating words in these two verses based on the Tafsir Al-Kassyaaf book. The focus of this study is to contain aspects in which one of the two aspects is lafadz (lafdzi). Judging from the lafadz it contains, Tikrar Lafdzi is a repetition of a verse from the Koran. To explain the topics discussed and collect various primary and secondary reference sources, the author of this article applies qualitative research methodology and Library Research-based data collection strategies. Tafsir Al-Kassyaaf functions as a primary source, while a number of related books and articles function as secondary sources. From writing this article, the author found findings based on the Tafsir Al-Kasyaaf book that First, the repetition of tikrar lafdzi in the lafadz العسر and يسرا counts twice in verses 5 and 6 to strengthen the meaning of the previous sentence. Second, in verses 5 and 6, the word العسر in the form of ma'rifah is marked alif lam, indicating that the difficulties referred to in the two verses are the same. On the other hand, the word يسرا in verses 5 and 6 is nakirah, so the ease stated in verse 5 is different from the ease stated in verse 6. Third, the word العسر which is in the form of ma'rifah and the word يسرا which is in the form of nakirah in verses 5 and 6 are understood one difficulty is simultaneously followed by two eases.